Understanding the Human-AI Interaction: Psychological and Social Impacts of AI Integration in Daily Life - Ani, Fauziah; Hamzah, Shahidah; Damin, Zahrul Akmal; Rameli, Norizan; Farid, Sumera (Journal of Techno-Social, 2025)
The rapid advancement of Artificial Intelligence (AI) is reshaping how individuals think, feel and interact in daily life. AI technologies now play a central role in supporting decision-making, offering emotional assistance and shaping digital communication. However, the long-term psychological and ethical effects of AI use remain underexplored, particularly in non-technical contexts. This study aims to examine the psychological and social impacts of AI integration through a systematic literature review (SLR) of 68 peer-reviewed articles published between 2013 and 2024. Articles were retrieved from key academic databases including PubMed, Scopus and Google Scholar. The review employed thematic analysis to identify patterns and gaps across studies related to human cognition, emotional behaviour and social dynamics. Findings reveal four major concerns. AI usage often leads to cognitive offloading, where users become less reliant on their own judgment. Emotionally, users may form attachments to AI systems despite their lack of true empathy. On a social level, AI algorithms can reinforce selective exposure, limit diverse viewpoints and contribute to echo chambers. Ethical issues also persist, especially involving bias and unequal access to AI resources. This review offers a novel, human-centred perspective by linking psychological theory with technological impacts which is an angle often overlooked in AI discourse. It calls for more inclusive and ethically guided AI development, as well as interdisciplinary and longitudinal research that can better inform policy and system design. Ultimately, the study contributes strategic insight for ensuring AI enhances human well-being without undermining autonomy, equity or social trust.